DESIGN CHARTS IN N-VISUAL LANGUAGE AND BUSINESS PROCESS MODELING - Oleg V. OLKHOVIK (Advanced Engineering Research)
Problems that permit solution of charts in N-Visual Language dealing with design and automatic code generation of the software information systems are described. Collecting of design diagrams in N-Visual Language with modeling business processes diagrams in various notations is considered.